Flexible glass : enabling thin, lightweight, and flexible electronics - Garner, Sean M. (Hoboken, NJ : John Wiley & Sons, Inc. ; Beverly, MA : Scrivener Publishing LLC, 2017)
This book details flexible glass properties that enable use in emerging electronic and opto-electronic applications. Discussion includes flexible glass advantages compared to alternative substrate materials. Examples describe flexible glass in processes such as vacuum deposition, monolithic integration, printing, and roll-to-roll. Flexible glass demonstrations in emerging applications such as photovoltaics, flexible displays, and optical interconnects are also detailed. The reader will find in this unique book: -Discussion of flexible glass processing and mechanical reliability.-Demonstration of flexible glass in roll-to-roll (R2R) fabrication processes.-Flexible glass substrate examples in displays, sensors, and photovoltaics.-Flexible glass ecosystem description for identification of new applications.
8.4 Thin Glass DisplaysReferences; Chapter 9: Guided-Wave Photonics in Flexible Glass; 9.1 Flexible Guided-Wave Photonics; 9.2 Flexible Polymer Passive Waveguide Photonics; 9.3 Flexible Polymer Active Waveguide Photonics; 9.4 Flexible Polymer Waveguides for Electro-Optic Applications; 9.5 Flexible Glass Optical Substrates; 9.6 Ultrafast-Laser Fabrication of Embedded Waveguides; 9.7 Embedded Waveguides in Flexible Glass; 9.8 Prospective of Thermal Poling in Flexible Glass Waveguides; 9.9 Summary and Future; References; Chapter 10: Flexible Glass for Microelectronics Integration.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 12, 2018).
Keywords: Thin films; Glass coatings; Electronic books